(Z)-Ethyl 2-benzylidene-3-oxobutanoate - Arif I. Ismiyev (Acta Crystallographica Section E, 2011)
The title molecule, C13H14O3, adopts a Z conformation about the C=C double bond. In the crystal, weak intermolecular C—H...O hydrogen bonds with phenyl –CH atoms functioning as donors and the carbonyl O atom of an ester group as acceptor are observed.